Distribution of Aedes aegypti, Aedes albopictus and Culex sp. and detection of Wolbachia among them in city district Lahore (Journal of Fatima Jinnah Medical University, 2019)
Background: Dengue is one of the important public health concerns world over is known to cause significant increase in overall disease burden in Pakistan. Since 2011, the disease has penetrated from urban to rural skirts of the most congested cities. A number of control measures have been tested but none of them is exhaustive. Wolbachia is most common parasite of arthropods and insects. Due to its heritable endosymbiosis relationship with mosquitoes, it has created interest among scientific community as a potential biological control agent. It infects wild dengue vector species and blocks the transmission of dengue virus through feminization, mutagenesis and parthenogenesis. In Pakistan, limited data is available regarding Wolbachia infestation among mosquito species therefore the present cross-sectional study was designed to detect the presence or absence of Wolbachia among wild mosquito species (Aedes aegypti, Aedes albopictus and Culex sp.) in the city district Lahore through Polymerase Chain Reaction (PCR) and to establish PCR model for easy detection of Wolbachia in mosquitoes.Materials and methods: Mosquito traps were set randomly in different areas of Lahore. Total 725 mosquitoes were captured and segregated into 76 pools. Housefly and Culex sp. were used as a control. DNA was isolated and subjected to PCR. Data was analyzed using SPSS version 15.Results: From total 725 mosquitoes, 564 were Aedes aegypti, 137 were Culex sp. and 24 were Aedes albopictus. Aedes aegypti and Aedes albopictus were all negative for Wolbachia. Only 3 out of 20 pools of Culex species were positive for Wolbachia pipientis. Housefly also showed none Wolbachia infestation.
Keywords: Wolbachia; Dengue; Aedes albopictus; Culex sp.; Polymerase Chain Reaction